The caveolin‐3 P104L mutation in LGMD‐1C patients inhibits non‐insulin‐stimulated glucose metabolism and growth but promotes myocyte proliferation. (13th May 2019) - Shang, Lina; Chen, Tingting; Xian, Jing; Deng, Yufeng; Huang, Yiyuan; Zhao, Qiwei; Liang, Guining; Liang, Zhifeng; Lian, Fang; Wei, Hongqiao; Huang, Qin
Abstract: The caveolin‐3 (CAV3) protein is known to be specifically expressed in various myocytes, and skeletal muscle consumes most of the blood glucose as an energy source to maintain normal cell metabolism and function. The P104L mutation in the coding sequence of the human CAV3 gene leads to autosomal dominant disease limb‐girdle muscular dystrophy type 1C (LGMD‐1C). We previously reported that C2C12 cells transiently transfected with the P104L CAV3 mutant exhibited decreased glucose uptake and glycogen synthesis after insulin stimulation. The present study aimed to examine whether the P104L mutation affects C2C12 cell glucose metabolism, growth, and proliferation without insulin stimulation. C2C12 cells stably transfected with CAV3‐P104L were established, and biochemical assays, western blot analysis and confocal microscopy were used to observe glucose metabolism as well as cell growth and proliferation and to determine the effect of the P104L mutation on the PI3K/Akt signaling pathway. Without insulin stimulation, C2C12 cells stably transfected with the P104L CAV3 mutant exhibited decreased glucose uptake and glycogen synthesis, decreased CAV3 expression and reduced localization of CAV3 and GLUT4 on the cell membrane. The P104L mutant significantly reduced the cell diameters, but accelerated cell proliferation. Akt phosphorylation was inhibited, and protein expression of GLUT4, p‐GSK3β, and p‐p70s6K, which are molecules downstream of Akt, was significantly decreased. The CAV3‐P104L mutation inhibits glycometabolism and cell growth but accelerates C2C12 cell proliferation by reducing CAV3 protein expression and cell membrane localization, which may contribute to the pathogenesis of LGMD‐1C.